(untitled) (Research, Society and Development, 2023)
The supervised internship as a mandatory curricular component in degree courses is very important for initial training. The purpose of consits this article is to highlight the contributions, experiences and reflections of the remote supervised internship for initial training in the field school during the Covid-19 pandemic, reflecting through the lived narratives. This article consists of a narrative qualitative research, these narratives in question are from the author’s experiences and experiences during the remote internship in the Degree in Biological Sciences course, a training research carried out through observation, the data were produced in a descriptive way, The field of research was a Technical Public School of the Federal Teaching Network, located in Teresina-PI, the internship was developed in a group of the First year of High School in the discipline of Biological Sciences, the narrated results demonstrate that the remote classes provided situations innovative, there was a low adherence of students to remote classes, the challenges and unforeseen situations were overcome, in view of this it is clear that the internship contributes to initial training and in the face of the pandemic scenario, remote teaching was the only viable alternative.